Novel insights by 4D Flow imaging on aortic flow physiology after valve-sparing root replacement with or without neosinuses. (1st February 2018) - Galea, Nicola; Piatti, Filippo; Sturla, Francesco; Weinsaft, Jonathan W; Lau, Christopher; Chirichilli, Ilaria; Carbone, Iacopo; Votta, Emiliano; Catalano, Carlo; De Paulis, Ruggero; Girardi, Leonard N; Redaelli, Alberto; et al.
Abstract: OBJECTIVES: This study was undertaken to evaluate the flow dynamics in the aortic root after valve-sparing root replacement with and without neosinuses of Valsalva reconstruction, by exploiting the capability of 4D Flow imaging to measure in vivo blood velocity fields and 3D geometric flow patterns. METHODS: Ten patients who underwent valve-sparing root replacement utilizing grafts with neosinuses or straight tube grafts (5 cases each) were evaluated by 4D Flow imaging at a mean of 46.5 months after surgery. We used in-house processing tools to quantify relevant bulk flow variables (flow rate, stroke volume, peak velocity and mean velocity), wall shear stresses and the amount of flow rotation characterizing the region enclosed by the graft and the aortic valve leaflets. RESULTS: Despite bulk flows with similar peak velocities, flow rates and stroke volumes ( P = 0.31–1.00), the neosinuses graft was associated with a lower mean velocity ( P < 0.03) and magnitude of wall shear stress along the axial direction of the vessel wall ( P < 0.05) at the proximal root level but remained comparable along the circumferential direction ( P = 0.22–1.0) to the straight tube graft. Flow rotation was evidently and systematically higher in the neosinuses grafts, characterized by streamline rotations higher than 270°, nearly triple that of tubular grafts (10.3 ÷ 14.0% of all aortic streamline vs 2.2 ÷ 5.7%, P = 0.008). CONCLUSIONS: Recreation of the sinuses of Valsalva during valve-sparing root replacement is associated with significantly lower wall shear stress and organized vortical flows at the level of the sinus that are not evident using the straight tube graft. These findings need confirmation in larger studies and could have important implications in terms of aortic valve durability.